1988
DOI: 10.1007/bf00008456
|View full text |Cite
|
Sign up to set email alerts
|

Crustacean zooplankton assemblages in freshwaters of tropical Australia

Abstract: Throughout tropical Australia eulimnetic zooplankton is composed of 7 calanoid copepods, 5 cyclopoid copepods and 12 cladocerans . A further 10 cyclopoids and 9 cladocerans occur as littoral `strays', making 43 species in all . Dominants include Diaptomus lumholtzi, Mesocyclops notius, Thermocyclops decipiens, Diaphanosoma excisum, Ceriodaphnia cornuta, and Moina micrura. Momentary species composition averages 1 .0 calanoids, 1 .3 cyclopoids and 2 .0 cladocerans . These assemblages are not only less complex th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
(40 reference statements)
0
20
1
Order By: Relevance
“…The same is true for aquatic invertebrates and the southern Carnarvon Basin appears to represent a zone where Bassian and Torresian biotic elements meet (see Serventy and Whittell, 1967). Examples of Torresian species that have extended their range southwards are the copepod Eudiaptomus lumholtzi (see Timms and Morton, 1988) and beetles Berosus dallasae and Hydroglyphus leai (see Watts, 1978Watts, , 1987. Examples of Bassian species extending north are the copepod Calamoecia tasmanica subattenuata (see Maly et al, 1997) and ostracods Mytilocypris mytiloides and Australocypris insularis (see De Deckker, 1978).…”
Section: Biogeographymentioning
confidence: 95%
See 1 more Smart Citation
“…The same is true for aquatic invertebrates and the southern Carnarvon Basin appears to represent a zone where Bassian and Torresian biotic elements meet (see Serventy and Whittell, 1967). Examples of Torresian species that have extended their range southwards are the copepod Eudiaptomus lumholtzi (see Timms and Morton, 1988) and beetles Berosus dallasae and Hydroglyphus leai (see Watts, 1978Watts, , 1987. Examples of Bassian species extending north are the copepod Calamoecia tasmanica subattenuata (see Maly et al, 1997) and ostracods Mytilocypris mytiloides and Australocypris insularis (see De Deckker, 1978).…”
Section: Biogeographymentioning
confidence: 95%
“…Shiel and Koste, 1979) et al (1997) known only from the Paroo River region of New South Wales (Frey, 1991). Occurrence in the Carnarvon Basin of the calanoid copepod Eudiaptomus lumholtzi, common in northern Australia including the Kimberley (Timms and Morton, 1988), is a 1200 km southwards extension of the western range of the species. Similarly, records from the Carnarvon Basin extend the range of the anostracan Branchinella probiscida 2000 km south-westwards (see Geddes, 1981).…”
Section: Aquatic Invertebratesmentioning
confidence: 99%
“…A more comprehensive study of the crustacean zooplankton of fresh waters in tropical Australia was that of Timms & Morton (1988). These authors found that throughout tropical Australia the eulimnetic zooplankton comprised 7 species of calanoid copepods, 5 of cyclopoid copepods and 12 of the Cladocera.…”
Section: Macrophytesmentioning
confidence: 99%
“…Ninety-six cladoceran species are known from tropical Australia, with up to 44 taxa recorded in areas of the Northern Territory and Queensland by Timms & Morton (1988), presumably including limnetic taxa. Twenty-eight of 35 cladoceran taxa recorded by Tait et al (1984) were littoral in habit; 37 of 43 recorded by Julli (1986) were littoral species.…”
Section: Macrophytesmentioning
confidence: 99%
“…Unfortunately, the type material of M. arnaudi is no longer available (Hamond, 1987), so the original description of Sars (1908), with its fine illustrations, is all that was left of the first Australian Metacyclops. An unnamed and as yet undescribed species of Metacyclops was reported by Timms and Morton (1988), but this genus does not appear to have a significant diversity in Australian surface waters, and certainly nothing that could be compared with other continents of the Southern Hemisphere (see Dussart and Defaye, 1985).…”
Section: Introductionmentioning
confidence: 99%